Leukocyte-Derived Microparticles in Vascular Homeostasis - Angelillo-Scherrer, Anne (Circulation research, 2012)
Leukocyte-derived microparticles (LMPs) may originate from neutrophils, monocytes/macrophages, and lymphocytes. They express markers from their parental cells and harbor membrane and cytoplasmic proteins as well as bioactive lipids implicated in a variety of mechanisms, maintaining or disrupting vascular homeostasis. When they carry tissue factor or coagulation inhibitors, they participate in hemostasis and pathological thrombosis. Both proinflammatory and anti-inflammatory processes can be affected by LMPs, thus ensuring an appropriate inflammatory response. LMPs also play a dual role in the endothelium by either improving the endothelial function or inducing an endothelial dysfunction. LMPs are implicated in all stages of atherosclerosis. They circulate at a high level in the bloodstream of patients with high atherothrombotic risk, such as smokers, diabetics, and subjects with obstructive sleep apnea, where their prolonged contact with the vessel wall may contribute to its overall deterioration. Numbering microparticles, including LMPs, might be useful in predicting cardiovascular events. LMPs modify the endothelial function and promote the recruitment of inflammatory cells in the vascular wall, necessary processes for the progression of the atherosclerotic lesion. In addition, LMPs favor the neovascularization within the vulnerable plaque and, in the ruptured plaque, they take part in coagulation and platelet activation. Finally, LMPs participate in angiogenesis. They might represent a novel therapeutic tool to reset the angiogenic switch in pathologies with altered angiogenesis. Additional studies are needed to further investigate the role of LMPs in cardiovascular diseases. However, large-scale studies are currently difficult to set up because microparticle measurement still requires elaborate techniques which lack standardization.